2016
DOI: 10.3892/br.2016.793
|View full text |Cite
|
Sign up to set email alerts
|

Increased complements and high-sensitivity C-reactive protein predict heart failure in acute myocardial infarction

Abstract: The aim of the present study was to investigate whether the serum levels of complements and high-sensitivity C-reactive protein (hs-CRP) in patients with acute myocardial infarction (AMI) are associated with the severity of myocardial injury. Consecutive patients (n=110) with AMI and 33 healthy individuals, who served as control subjects, were enrolled from May 2013 to February 2015. These patients were divided into two groups, those with ST segment elevation MI (STEMI) and those with non-ST segment elevation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 29 publications
1
10
0
1
Order By: Relevance
“…It was stated that the increased CRP levels in the patients with HF may be a consequence of an ischemic necrosis that initiate this potent inflammatory stimulus 36 . Our results are in accordance with the study of Liu et al 37 that reported a positive correlation between the increased CRP level and the increased level of serum complement factors C3, C4, C5b9 in the HF patients.…”
Section: Discussionsupporting
confidence: 93%
“…It was stated that the increased CRP levels in the patients with HF may be a consequence of an ischemic necrosis that initiate this potent inflammatory stimulus 36 . Our results are in accordance with the study of Liu et al 37 that reported a positive correlation between the increased CRP level and the increased level of serum complement factors C3, C4, C5b9 in the HF patients.…”
Section: Discussionsupporting
confidence: 93%
“…Circulating levels of C-reactive protein (CRP) have been shown to be linked to poor prognosis in patients with atherothrombotic problems, heart failure, arrhythmias, and myocarditis.3 Fourteen predictors of heart failure were studied by Ho et al4,5 Important predictors identified were older age, diabetes mellitus, valvular disease, hypertension, higher heart rate, left ventricular hypertrophy, left bundle branch block, cardiovascular disease, body mass index, smoking, gender, and dyslipidemia 4,5. Few studies have reported the association between high sensitivity C-reactive protein (hsCRP) and heart failure after ACS 6,7. High levels of hsCRP at myocardial infarction also predict early mortality 6,8.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Kavsak et al (18) showed that high CRP titers, independent of age, sex, and troponin I concentration, predicted a long-term heart failure and mortality. Liu et al (19) reported that both hsCRP and brain natriuretic peptide (BNP) levels, measured 30 days after an ACS, were independently associated with the risk of heart failure and cardiovascular mortality, with the highest risk occurring when both markers were simultaneously high. Al Aseri et al (20) also established a correlation between elevated hsCRP values and the incidence of cardiac insufficiency.…”
Section: Discussionmentioning
confidence: 99%